The Impact of Teachers' Perceptions and Readiness on Their Performance in the Implementation of the Independent Learning Curriculum - Zaini, Mohammad (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This research aims to analyze the influence of teacher perceptions and readiness on teacher performance in the Independent Learning Curriculum in one of the madrasah in East Java. This research uses quantitative methods with an explanatory and survey approach. The questionnaire was prepared based on research variables: perception, teacher readiness, and teacher performance. Research data was taken from 130 teachers who were the samples for this research using random sampling techniques. Data analysis uses multiple linear regression. The research results show a significant influence of perception on teacher performance in the Independent Learning Curriculum in madrasah. Additionally, teacher readiness significantly impacts teacher performance in the Independent Learning Curriculum in Madrasah. Overall, teacher perception and readiness significantly influence teacher performance in the Independent Learning Curriculum in madrasah. This research provides implications regarding the importance of paying attention to teachers' perceptions and readiness to improve their performance. By understanding and managing these factors, madrasah can be more effective in implementing new curricula and achieving desired educational goals.